Temporal Trends in Emergency Medical Services and General Practitioner Use for Acute Stroke After Australian Public Education Campaigns - Bray, Janet; Finn, Judith; Cameron, P.; Smith, K.; Straney, L.; Cartledge, S.; Nehme, Z.; Lim, M.; Bladin, C. (Lippincott Williams & Wilkins, 2018)
Background and Purpose- The Australian Stroke Foundation ran annual paid advertising between 2004 and 2014, using the FAST (Face, Arm, Speech, Time) campaign from 2006 and adding the message to call emergency medical services in 2007. In this study, we examined temporal trends in emergency medical services use and referrals from general practitioners in the Australian state of Victoria to evaluate the impact of these campaigns. Methods- Using data from 33 public emergency departments, contributing to the Victorian Emergency Minimum Dataset, we examined trends in emergency department presentations for 118?000 adults with an emergency diagnosis of stroke or transient ischemic attack between 2003 and 2015. Annual trends were examined using logistic regression using a precampaign period (January 2003 to August 2004) as reference and adjusting for demographic variables. Results- Compared with the precampaign period, significant increases in emergency medical services use were seen annually between 2008 and 2015 (all P<0.001, eg, 2015; adjusted odds ratio, 1.16; 95% CI, 1.10-1.23). In contrast, a decrease was seen in patients presenting via general practitioners across all campaign years (all P<0.001, eg, 2015; adjusted odds ratio, 0.48; 95% CI, 0.44-0.53). Conclusions- Since the Stroke Foundation campaigns began, a greater proportion of stroke and transient ischemic attack patients are presenting to hospital by emergency medical services and appear to be bypassing their general practitioners.